Transcriptome and WGCNA analysis revealed the molecular mechanism of drought resistance in new sugarcane varieties - Wang, Ziyuan; Yin, Shihang; Wei, Yanli; Chen, Baoshan; Li, Wenlan (Frontiers in Plant Science, 2025)
IntroductionDrought stress is a major abiotic factor limiting sugarcane productivity. However, the molecular mechanisms conferring drought resistance in sugarcane are not fully elucidated, which hinders the breeding of resilient varieties.MethodsThree experimental sugarcane varieties were subjected to polyethylene glycol (PEG6000)-simulated drought stress. Subsequent transcriptomic analysis was performed by integrating second-generation (Illumina) and third-generation (PacBio) sequencing technologies. This approach yielded a comprehensive transcriptome landscape. Bioinformatics analyses included gene annotation, differential expression screening, Weighted Gene Co-expression Network Analysis (WGCNA), and network visualization using Cytoscape.ResultsSequencing generated a total transcript length of 77,930,985 bp, identifying 40,359 unique genes, with 38,791 successfully annotated. Under drought stress, the variety ZZ9 exhibited significant enrichment and upregulation of metabolic pathways related to photosynthesis, plant hormones, polysaccharide synthesis, and amino acid metabolism. Several transcription factor families, including bHLH, bZIP, ERF, NAC, MYB, and GRAS, were drought-inducible. WGCNA identified 22 co-expression modules, with the MEten module showing the highest correlation with drought response. Key hub genes within MEten included NACA1, ABA-related genes, ERA1, PER70, ATX, two superoxide dismutase genes (SODF1 and SODF2), two late embryogenesis abundant (LEA) genes, and two lipoxygenase (LOX) genes. Furthermore, Cytoscape-based analysis pinpointed the novel gene PSY1 and two additional candidates potentially involved in photosynthetic regulation during drought.DiscussionBy integrating multi-platform transcriptomics and systems biology approaches, this study delineates potential molecular regulatory networks underlying drought resistance in sugarcane. The identified hub genes and pathways provide critical resources for future functional genomics studies and molecular breeding programs aimed at enhancing drought tolerance in sugarcane.